2020
DOI: 10.1002/ccd.29136
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a contrast media volume control device on acute kidney injury rate in patients with acute coronary syndrome

Abstract: BACKGROUND The DyeVert™ system (Osprey Medical Inc., Minnesota, MN) may reduce contrast media (CM) volume during coronary procedures while maintaining fluoroscopic image quality. Here, we assessed whether the use of the DyeVert system reduces acute kidney injury (AKI) rate in patients with acute coronary syndrome (ACS) undergoing invasive coronary procedures. METHODS ACS patients scheduled for coronary procedure from January 2017 to December 2019 were included. Two groups were identified: (a) Control group (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 35 publications
(74 reference statements)
1
29
0
Order By: Relevance
“…Nine studies reported on adverse events and no DyeVert System-related adverse events were reported ( 27 , 28 , 30 , 35 – 39 , 42 ). Corcione et al described a case of contrast-induced nephropathy in a patient who underwent a combined carotid angiography and angioplasty and experienced elevated serum creatinine levels that returned to baseline 3 days after the procedure; the authors noted the event was not device-related ( 38 ).…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies reported on adverse events and no DyeVert System-related adverse events were reported ( 27 , 28 , 30 , 35 – 39 , 42 ). Corcione et al described a case of contrast-induced nephropathy in a patient who underwent a combined carotid angiography and angioplasty and experienced elevated serum creatinine levels that returned to baseline 3 days after the procedure; the authors noted the event was not device-related ( 38 ).…”
Section: Resultsmentioning
confidence: 99%
“…This CM volume reduction translated in a lower incidence of CI-AKI in a study of 451 patients undergoing coronary procedures for acute coronary syndromes (DyeVert™: 8% vs. Control: 19%) [76].…”
Section: Contrast Removal Strategiesmentioning
confidence: 97%
“…In the AVERT trial, AVERT™ system, in spite of having demonstrated a decrease in the volume of CM compared to traditional methods, failed to accomplish a reduction in the incidence of contrast induced nephropaty (CIN), suggesting that the obtained reduction in the volume of CM that had been obtained was not sufficient to reduce the incidence of AKI [24]. The DyeVert™ system has been recently assesed in a retrospective analysis [25] of 112 patients with ACS undergoing primary PCI: use DyeVert resulted in lower contrast media used (130 [120-188] mL vs. 99 mL; p < 0.001) and lower incidence of contrast induced AKI (odds ratio [OR] = 0.37; 95% confidence interval [CI] 0.14-0.95; p = 0.047) compared to propensity score matched controls. An ongoing trial (ClinicalTrials.gov Identifier: NCT04714736) is assessing DyeVert™ system in ACS setting.…”
Section: Acute Kidney Injurymentioning
confidence: 99%